(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
Wave energy converters (WECs) that harness energy from multiple degrees-of-freedom (DOFs) have the potential to improve power performance across a wide spectrum of wave conditions. Many subsurface WECs are multi-modal, or designed to capture power from multiple DOFs to offset losses from wave orbital decay. However, multi-modal WECs require sophisticated control strategies and careful hydrodynamic analysis to tune each DOF, as coupling between rigid body modes can lead to non-linear behavior and reduced performance. This study experimentally analyzes how the rigid body modes of a submerged cylindrical WEC vary with wave period and affect the device’s dynamics and power production in both single and three-tether configurations. Power lost due to the presence of non-linear behavior is estimated by comparing experimental results with a linear time-domain model. In regular waves, results show that surge-pitch coupling is more prevalent than heave-pitch coupling. Additionally, the device predominantly captures power through heave, as it is resonant with the incident wave for all but the longest periods. Results suggest better power performance when both heave and surge are resonant in comparison to heave and pitch, indicating both heave and surge should be tuned to be resonant with the incident wave. Experimental results also show that as the pitch angle increases, so do the non-linear dynamics caused by surge-pitch coupling, leading to subharmonic device motions and suboptimal power production. Consequently, periods that result in large pitch angles show the greatest discrepancies from power estimates provided by linear models. These results emphasize the importance of tuning a device’s response in all rigid body modes to avoid subharmonic excitation. They also suggest that numerical models capable of incorporating non-linearities from large amplitude motions are necessary to more accurately predict the response and power potential of submerged WECs free to oscillate in surge, heave, and pitch.